Acute Exercise-Induced Set Shifting Benefits in Healthy Adults and Its Moderators: A Systematic Review and Meta-Analysis - Oberste, Max; Sharma, Sophia; Bloch, Wilhelm; Zimmer, Philipp (Frontiers in Psychology, 2021)
Background: Positive effects of acute exercise on cognitive performances inspired research that investigated the effects of acute exercise on specific cognitive subdomains. Many existing studies examined beneficial effects of acute exercise on set shifting performance. Set shifting, a subdomain of executive function, is the ability to switch between different cognitive sets. The results of existing studies are inconsistent. Therefore, a meta-analysis was conducted that pooled available effect sizes. Additionally, moderator analyses were carried out to identify covariates that determine the magnitude of exercise-induced set shifting benefits. Methods: Medline, PsycINFO, and SPORTDiscus were searched for eligible studies. Hedges’ g corrected standardized mean difference values were used for analyses. Random-effects weights were applied to pool effects. Potential moderation of the effect of acute exercise on subsequent set shifting performance by exercise intensity, type of exercise, participants’ age, and type of control group were examined. Results: Twenty-two studies (N=1,900) were included into analysis. All aggregated effect sizes ranged from small to moderate. Overall, a small significant beneficial effect was revealed (g = -.32, 95 % CI -.45 to -.18). Heterogeneity of included effect sizes was moderate and significant (т² = .0715, I² = 46.4%, (p<.0016). Moderator analyses revealed a larger average effect in older adults than for studies examining younger adults (-.42 vs. -.29). Light exercise (-.51) led to larger effects than moderate (-.24) or vigorous exercise (-.29). Studies testing acute exercise against active con-trol groups showed a noticeably smaller average effect (-.13) than studies that used passive (-.38) or cognitive engaging control groups (-.34). Interestingly, application of resistance or aerobic exercise led to no different average effect sizes (-.30 vs. -.32). However, none of the tested covariates reached statistical significance. Conclusion: Acute exercise improves subsequent set shifting performance. However, effect sizes are small, making the relevance for everyday life questionable. The results indicate that older adults benefit more from acute exercise than younger adults do. Light intensity exercise seems most effective while the type of exercise does not seem to influence the magnitude of effects. Research designs with active control groups show the smallest average effect, raising concerns about placebo effects.